Gaya Bahasa Sindiran dalam Lirik Lagu Pesta Para Babi Pembangunan Karya Pari Kesit - Nila Repalia; Revi Vella Zetira; Resa Alifia; Sumarno Sumarno (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2026)
This study aims to describe the forms of satirical language styles found in the lyrics of Pesta Para Babi Pembangunan by Pari Kesit. This research employed a qualitative descriptive method using a stylistic approach to examine language as a medium for conveying social criticism. The research data consisted of words, phrases, and sentences containing satirical language styles in the song lyrics. Data were collected through observation and note-taking techniques, while data analysis was conducted by identifying, classifying, and interpreting the types of figurative language based on stylistic theory. The findings revealed three types of satirical language styles in the lyrics: irony, cynicism, and sarcasm. Irony is used to express criticism indirectly through meanings that contrast with the literal expressions. Cynicism reflects doubt and distrust toward development policies, while sarcasm serves as a strong and direct form of criticism against parties considered responsible for harming indigenous communities. These satirical expressions function as a medium of social criticism toward development practices that are perceived to neglect the interests of indigenous peoples and have negative impacts on environmental sustainability. The study concludes that song lyrics function not only as artistic expressions but also as effective communication media for delivering social messages, raising public awareness, and encouraging critical reflection on development-related issues.